The expected benefits of trade liberalization for world income and development: Opening the “black box” of global trade modeling - Bouët, Antoine (International Food Policy Research Institute, 2008)
Trade liberalization is expected to act positively on world economic development and poverty alleviation, both of which have become high priorities of the international community. This emphasis explains why numerous studies have focused on assessing the expected benefits of trade liberalization on development. The main empirical tools for these assessments have been the use of spatial and nonspatial partial equilibrium models, gravity equations, and single- and multicountry computable general equilibrium models (CGEMs). Multicountry CGEMs, however, have produced strikingly divergent results. As demonstrated by recent studies, the associated increase in world welfare from full trade liberalization ranges from 0.2 to 3.1 percent—results that differ by a factor of 15! The objective of this study is to examine the efficiency of trade modeling in capturing the benefits from trade liberalization. It provides a survey of methodologies utilized to assess the impact of trade liberalization, putting an emphasis on multicountry CGEMs, and examines the extent to which such assessments diverge. The survey also demonstrates the benefits of “complementary analysis,” which utilizes different methodologies to study a specific topic. The report presents global modeling results using a general equilibrium model—the modeling international relations under applied general equilibrium (MIRAGE) model—the results of which are compared to those obtained in recent studies. Using the MIRAGE model,1 full trade liberalization is estimated to increase world real income by US$100 billion (+0.33 percent) after 10 years of implementation. This trade reform would be development-friendly, as it entails a larger growth rate of real income for developing countries and especially for least-developed countries.